MENINGKATKAN KEMAMPUAN BERPIKIR KRATIF SISWA MELALUI PENDEKATAN OPEN-ENDED PROBLEM PADA MATERI CAHAYA KELAS VIII SMPN 17 PEKANBARU - Rahmawati '; Azhar '; Zulhelmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to describe the creative thinking abilities of students in the class that implements the learning physics by open-ended problem approach and the class of conventional learning and find a significant difference in creative thinking abilities of students between classes that implement learning physics by open-ended problem approach and class conventional learning the light lesson grade VIII at JHS 17 Pekanbaru. The study population was all students of JHS 17 Pekanbaru grade VIII and the samples is grade VIII-6 as the experimental class and grade VIII-5 as the control class. Data collection instrument in this research is to test creative thinking that consists of four items essay. Analysis of the data in this research is descriptive and inferensial. The result of analysis descrptive had shown that average absorption experiment class was 79.81% on both categories, the average absorption control class is 69.97% with the category quite well. There are differences between creative thinking abilities of students learning physics by open-ended problem approach with conventional physics learning. The learning physics by open-ended problem approach can improve creative thinking abilities of students in the learning process in grade VIII-6 JHS 17 Pekanbaru.Key Word: Creative thinking ability, Open-ended problem approach, The light.